Padronização de modelos experimentais para investigação de produtos naturais biologicamente ativos com potenciais antidiabético e hipolipemiante em ratos wistar - Siqueira, Vera Lúcia Dias (2003)
Experimental models using lab animals have an important role in the pharmacological studies of new drugs. However, an appropriated choice of each model must be performed, since a perfect animal model does not exist. Thus, the objective of this study was to standardize experimental models to investigate natural products with biological activity (NPBA) by using Wistar rats. The rat models were constituted to evaluate the acute and chronic antidiabetic and hypolipidemic effect of some NPBAs. We observed that the Wistar rats showed the expected effect after the administration of acarbose, chitosan, insulin or orlistat, representing animal models for investigation of NPBAs with antidiabetic and hypolipidemic potential. However, the response to sinvastatin or ciprofibrate was different from that observed in humans. Thus, Wistar rats could be used in pharmacological screenings to evaluate NPBAs with hypolipemic potential since it is taken into account this difference. In addition, alloxan-diabetic rats, in spite of partial reversion of diabetes, could be adequate experimental model to investigate NPBAs with antidiabetic effects. However, a tendency to restore the normal serum lipids concentrations limits the use of alloxan-diabetic rats for evaluation of NPBAs with hypolipidemic potential. Finally, the Solanum melongena and the Cissus sicyoides, used in our experiments did not show antidiabetic and hypolipidemic effect.